Take-Home Exams in Higher Education: A Systematic Review - Lars Bengtsson (MDPI AG, 2019)
This work describes a systematic review of the research on take-home exams in tertiary education. It was found that there is some disagreement in the community about the virtues of take-home exams but also a lot of agreement. It is concluded that take-home exams may be the preferred choice of assessment method on the higher taxonomy levels because they promote higher-order thinking skills and allow time for reflection. They are also more consonant with constructive alignment theories and turn the assessment into a learning activity. Due to the obvious risk of unethical student behavior, take-home exams are not recommended on the lowest taxonomy level. It is concluded that there is still a lot of research missing concerning take-home exams in higher education and some of this research may be urgent due to the emergence of massive online open courses (MOOCs) and online universities where non-proctored exams prevail.